Construction of three-dimensional, homogeneous regenerative cartilage tissue based on the ECG-DBM complex - Liu, Jingwen; Chen, Feifan; Song, Daiying; Zhang, Qixin; Li, Peizhe; Ci, Zheng; Zhang, Wei; Zhou, Guangdong (Frontiers in Bioengineering and Biotechnology, 2023)
The feasibility of using a steel (decalcified bone matrix, DBM)-reinforced concrete (engineered cartilage gel, ECG) model concept for in vivo cartilage regeneration has been demonstrated in preliminary experiments. However, the regenerated cartilage tissue contained an immature part in the center. The present study aimed to achieve more homogeneous regenerated cartilage based on the same model concept. For this, we optimized the culture conditions for the ECG-DBM complex based on the previous model and systematically compared the in vitro chondrogenic abilities of ECG in the cartilage slice state and the ECG-DBM complex state. We then compared the in vivo cartilage regeneration effects of the ECG-DBM complex with those of an equivalent volume of ECG and an equivalent ECG content. Significant increases in DNA content, and cartilage-specific matrix content were observed for the ECG-DBM complex compared with the ECG cartilage slice, suggesting that the DBM scaffold significantly improved the quality of ECG-derived cartilage regeneration in vitro.In the in vivo experiments, high-quality cartilage tissue was regenerated in all groups at 8 weeks, and the regenerated cartilage exhibited typical cartilage lacunae and cartilage-specific extracellular matrix deposition. Quantitative analysis revealed higher chondrogenic efficiency in the ECG-DBM group.Specifically, the ECG-DBM complex achieved more homogeneous and stable regenerated cartilage than an equivalent volume of ECG and more mature regenerated cartilage than an equivalent ECG content. Compared with ECG overall, ECG-DBM had a more controllable shape, good morphology retention, moderate mechanical strength, and high cartilage regeneration efficiency. Further evaluation of the ECG-DBM complex after in vitro culture for 7 and 14 days confirmed that extended in vitro preculture facilitated more homogeneous cartilage regeneration.